A Brief Report of Pingdi Landslide (23 July 2019) in Guizhou Province, China - Tao Yan (Geosciences, 2019)
This short communication reports on a large landslide with a movement of 2 million m3 of soil and rock that occurred on 23 July, 2019 in the village of Pingdi, located in the county of Shuicheng, Guizhou Province, China. This landslide resulted in 42 deaths and 9 missing people. This report describes the preliminary investigation, rescue effort, and possible cause. The total rainfall in the 6 days prior to the landslide was 189.1 mm, which may be held responsible as the major cause. Some recommendations are proposed to reduce human casualties and property losses.